Echium oil provides no benefit over linseed oil for (n-3) long-chain PUFA biosynthesis in rainbow trout - B Cleveland; David Francis; Giovanni Turchini (2012)
The implementation of alternative lipid sources for use in aquaculture is of considerable interest globally. However, the possible benefit of using stearidonic acid (SDA)–rich fish oil (FO) alternatives has led to scientific confusion. Two hundred and forty rainbow trout (Oncorhynchus mykiss) were fed 1 of 4 diets (3 replicate tanks/treatment) containing either FO, linseed oil (LO), echium oil, or mixed vegetable oil (72% LO, 23% sunflower oil, and 6% canola oil) as the dietary lipid source (16.5%) for 73 d to investigate the competition and long-chain PUFA (LC-PUFA) biosynthesis between the fatty acid substrates α-linolenic acid (ALA) and SDA. SDA was more efficiently bioconverted to LC-PUFA compared with ALA. However, when the dietary lipid sources were directly compared, the increased provision of C18 PUFA within the LO diet resulted in no significant differences in (n-3) LC-PUFA content compared with fish fed the other diets. This study therefore shows that, rather than the previously speculated substrate competition, the limiting process in the apparent in vivo (n-3) LC-PUFA biosynthesis appears to be substrate availability. Rainbow trout fed the SDA- and ALA-rich dietary lipid sources subsequently had similar significant reductions in (n-3) LC-PUFA compared with fish fed the FO diet, therefore providing no additional dietary benefit on (n-3) LC-PUFA concentrations.